Hybrid cloud computing: Security Aspects and Challenges - Umakant Bhaskar Gohatre, (AG Volumes, 2022)
Innovative business results may be achieved via the growth of cloud infrastructures to hybrid cloud models, which are driven by the need for increased Information technology (IT) agility and overall cost control constraints Hybrid cloud solutions integrate advantages of both public and private cloud infrastructures. Different security risks have been proven to be addressed in order to get the most out of the hybrid cloud approach. The security of hybrid clouds for major corporations and governments is the subject of this article. It explores numerous security types inside the IaaS and SaaS concepts, different authentication and security principles, and security difficulties in this field. In this case, a comparative assessment of several current solutions and the common issue areas and security threads are the focus of this work.